2009
DOI: 10.1007/s00415-009-0128-7
|View full text |Cite
|
Sign up to set email alerts
|

Delusions in frontotemporal lobar degeneration

Abstract: We assessed the significance and nature of delusions in frontotemporal lobar degeneration (FTLD), an important cause of young-onset dementia with prominent neuropsychiatric features that remain incompletely characterised. The case notes of all patients meeting diagnostic criteria for FTLD attending a tertiary level cognitive disorders clinic over a three year period were retrospectively reviewed and eight patients with a history of delusions were identified. All patients underwent detailed clinical and neurops… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
2
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 26 publications
3
31
2
2
Order By: Relevance
“…31 Interestingly, we observed differences in symptoms across both types, with psychosis being more common in behavioral-dominant FTD-MND and parkinsonism and limb apraxia being more common in language-dominant FTD-MND. Likewise, psychosis is associated with the behavioral variant of FTD but not the language variant of FTD, 32 and therefore our findings in FTD-MND mirror findings in FTD. Limb apraxia has not been emphasized previously in patients with FTD-MND, but in our study we showed that almost 50% of patients with language-dominant FTD-MND have limb apraxia.…”
Section: Discussionsupporting
confidence: 78%
“…31 Interestingly, we observed differences in symptoms across both types, with psychosis being more common in behavioral-dominant FTD-MND and parkinsonism and limb apraxia being more common in language-dominant FTD-MND. Likewise, psychosis is associated with the behavioral variant of FTD but not the language variant of FTD, 32 and therefore our findings in FTD-MND mirror findings in FTD. Limb apraxia has not been emphasized previously in patients with FTD-MND, but in our study we showed that almost 50% of patients with language-dominant FTD-MND have limb apraxia.…”
Section: Discussionsupporting
confidence: 78%
“…55 VHs are more common in the right than in the left temporal variant frontotemporal lobar degeneration, 56 often associated with delusions. 57 Imaging Features. While atrophy in the anterior temporal and medial frontal lobes is characteristic of frontotemporal lobar degeneration (On-line Fig 4), 58 specific imaging findings can reflect underlying subtypes.…”
Section: 45mentioning
confidence: 99%
“…Delusions are false beliefs that are incomprehensible, incorrigible, and held with subjective conviction despite proof or evidence to the contrary [27]. Although they are infrequent [10,36], they may occur in up to 14% of patients with bvFTD, particularly if they belong to specific subgroups [31,44,58]. Two of our patients have morbid jealousy or the Othello syndrome, a delusional belief that their spouse or sexual partner was unfaithful.…”
Section: Discussionmentioning
confidence: 97%